Answer:
(a) For 2010, f(x) = 6357.024×(1 + 0.017)ˣ
(b) f(25) = 8185.93
Explanation:
The initial population of the town in 2012 = 6575
The population growth rate = 1.7%
The exponential growth model is f(x) = a(1 + r)ˣ
Where;
a = The initial value = 6575
r = The rate of growth = 1.7%
x = The number of years,
Therefore, we have;
In 2010, we have f(x) = 6575(1 + 0.017)⁻² ≈ 6357.024
Therefore, the equation becomes;
f(x) = 6357.024×(1 + 0.017)ˣ
(b) In 2025, we have;
x = 2025 - 2012 = 13 years
∴ f(x) = 6575(1 + 0.017)¹³ = 8185.93